2012
DOI: 10.5511/plantbiotechnology.12.1002a
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an extraplastidic β-amylase which accumulates in the radish taproot influences the starch content of Arabidopsis thaliana

Abstract: Recent studies have revealed that β-amylases (EC 3.2.1.2) located in plastids participate in endogenous starch degradation. On the other hand, many plants possess a respectable amount of extraplastidic β-amylases. Because of their existence outside of the plastids, it has been believed that extraplastidic β-amylases do not contribute to starch degradation in plants. Here, we investigated the role of the major extraplastidic β-amylase of the radish (Raphanus sativus) (RsBAMY1) in starch metabolism. Amylase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
4
0
2
Order By: Relevance
“…Similarly, three transcripts (CL1841.Contig1, CL2019.Contig1 and Unigene1147) encoding beta-amylase, starch degradation related gene, were also up-regulated in three libraries. This finding is similar to that of Takahashi et al ( 2012 ) and Hara et al ( 2009 ) in which beta-amylases activity was elevated in the growing taproot of the radish, where starch content increased, implying that beta-amylases may be storage proteins in plant taproot (Gana et al, 1998 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, three transcripts (CL1841.Contig1, CL2019.Contig1 and Unigene1147) encoding beta-amylase, starch degradation related gene, were also up-regulated in three libraries. This finding is similar to that of Takahashi et al ( 2012 ) and Hara et al ( 2009 ) in which beta-amylases activity was elevated in the growing taproot of the radish, where starch content increased, implying that beta-amylases may be storage proteins in plant taproot (Gana et al, 1998 ).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the fact that the detailed mechanism is unclear, it is reported that β ‐amylase is also involved in hypocotyl thickening through degradation of starch and accumulation of soluble sugars (Takahashi et al . ). Thus, for the efficient hypocotyl growth, gene expressions and activities of these proteins must be regulated coordinately.…”
Section: Discussionmentioning
confidence: 97%
“…It was also reported that the hypocotyl sink activity is related to the activity of β ‐amylase that localizes in the cambia of the hypocotyl cortex (Takahashi et al . ) in several varieties of radish plants (Hara et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Seong et al(2016) Table 1과 같다. 기존 연구결과에 따르면 무의 근육에서 측정되는 전분 가수분해 활성의 대 부분은 β-amylase에 의한 것이므로 생성된 환원당 함량을 이용하여 β-amylase 활성을 결정하였다 (Hara et al, 2009b;Takahashi et al, 2012). 본 연구에서 이용한 무의 β-amylase 활성은 최대 169±17 total unit/g에서 최소 41.6±1.3 total unit/g 으로 나타났으며 평균값은 93.2±38.0 total unit/g으로 각 시료에 따라 최대 4배 가량 큰 차이를 보였다.…”
Section: 결과 및 고찰unclassified
“…또, 맥주 발효에 있어 맥아 생산 시 형성되는 β-amylase는 가장 중요한 발효 영향 인자로 잘 알려져 있다. 무의 경우 β-amylase 활성은 특히 무의 전분 함량 및 대사 과정과 밀접한 관련 이 있다고 보고된 바 있으며(Takahashi et al, 2012) 특정 β-amylase의 활성 정도에 따라 단맛이 우수한 품종을 선별할 수 있다…”
unclassified